Information Retrieval Architecture and Algorithms - Kowalski, Gerald; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
This text presents a theoretical and practical examination of the latest developments in Information Retrieval and their application to existing systems. By starting with a functional discussion of what is needed for an information system, the reader can grasp the scope of information retrieval problems and discover the tools to resolve them. The book takes a system approach to explore every functional processing step in a system from ingest of an item to be indexed to displaying results, showing how implementation decisions add to the information retrieval goal, and thus providing the user with the needed outcome, while minimizing their resources to obtain those results. The text stresses the current migration of information retrieval from just textual to multimedia, expounding upon multimedia search, retrieval and display, as well as classic and new textual techniques. It also introduces developments in hardware, and more importantly, search architectures, such as those introduced by Google, in order to approach scalability issues. About this textbook: A first course text for advanced level courses, providing a survey of information retrieval system theory and architecture, complete with challenging exercises Approaches information retrieval from a practical systems view in order for the reader to grasp both scope and solutions Features what is achievable using existing technologies and investigates what deficiencies warrant additional exploration
Information Retrieval System Functions -- Data Structures and Mathematical Algorithms -- Indexing -- Search -- Document and Term Clustering -- Information Presentation -- Search Architecture -- Information System Evaluation.
Keywords: Computer science; Information storage and retrieval systems; Computer Science; Information Storage and Retrieval; Data Storage Representation